(untitled) (Research, Society and Development, 2021)
The clinical conditions of a woman before pregnancy are quite different from those with an ongoing pregnancy. Physiological changes presented during pregnancy and that make women vulnerable were at high risk when associated with covid-10. The main objective of this study was to identify the main nursing care provided to pregnant women with heart disease contaminated by covid-19 and, more specifically, to describe the main nursing diagnoses in pregnant women with heart disease infected by covid-19 and to identify the main nursing interventions in pregnant women with heart disease contaminated by covid-19. This is a descriptive research, with a search for articles carried out in digital libraries. It was observed that, despite research showing that pregnant women are at greater risk for infection by covid-19, some authors noted that the consequences for the fetus and newborn can also be serious, especially if the infection occurs in the last trimester. of pregnancy. It is essential that humanized and individualized care remains present, as pregnant women are part of a group of patients who need critical attention due to their physiological and immunological changes.